Controversies in analytical psychology - Withers, Robert, 1952- (Hove, East Sussex ; New York : Brunner-Routledge, 2003)
Picks up on divisions within the area of analytical psychology and explores many of the most hotly contested issues, with a group of leading international Jungian authors contributing papers from contrasting perspectives.
Book Cover; Title; Contents; Biographical details of contributors; Acknowledgements; Introduction; Prospects for the Jung/Klein synthesis; Introduction; With healing in her wings: integration and repair in a self-destructive adolescent; Classical Jungian comment; Kleinian comment; Response to commentaries by Julian David and Robert Hinshelwood; The status of developmental theory; Introduction; Uneasy ghosts: theories of the child and the crisis in psychoanalysis; Jung, Jungians and the idea of birth trauma; Transference, countertransference and beyond; Introduction.
Includes bibliographical references and index.
Print version record.
Keywords: Psychoanalysis; Jungian psychology; Psychoanalytic counseling; Psychoanalysis; Jungian Theory; Psychoanalytic Therapy; Psychoanalysis; PSYCHOLOGY -- Movements -- Psychoanalysis; Jungian psychology; Psychoanalysis; Psychoanalytic counseling; Electronic books